Medication Lubricants for Oral Delivery of Drugs: Oral Processing Reduces Thickness, Changes Characteristics, and Improves Dissolution Profile - Marwa A. Malouh; Julie A. Y. Cichero; Yu Sun; Esther T. L. Lau; Lisa M. Nissen; Kathryn J. Steadman (MDPI AG, 2024)
Swallowing oral solid dosage forms is challenging for those who have medication swallowing difficulties, including patients with dysphagia. One option is to mix the drug (whole or crushed) with a thick vehicle (medication lubricant). Previous in vitro studies consistently suggest that thick vehicles could impact the dissolution of solid dosage forms, potentially influencing their therapeutic effectiveness, but do not account for changes that happen during oral processing and swallowing. This study aims to investigate the potential impact of medication lubricants on drug release and examine the effect of oral processing. In vitro dissolution of whole and crushed paracetamol tablets mixed with five commercially available medication lubricants (two IDDSI level 2, two IDDSI level 3, and one IDDSI level 4) were tested with and without oral processing; a medication lubricant with/without paracetamol was placed in the mouth (five healthy volunteers), prepared for swallowing, but then expectorated and assessed for physical characteristics and drug release. Medication lubricants, both alone and mixed with crushed paracetamol tablets, showed a significant decrease in viscosity after oral processing. Without oral processing, IDDSI level 3 and 4 lubricants significantly delayed the dissolution of paracetamol tablets. After oral processing, particularly with crushed tablets, there was a substantial increase in the dissolution rate. These findings suggest that dissolution testing overestimates the impact of medication lubricants on drug dissolution. Therefore, using in vitro dissolution tests to predict the dissolution rate of medications mixed with thick vehicles is discouraged. It is essential to consider ways to incorporate the effects of the oral environment and oral processing on thick vehicles used for oral medication administration.